Ethical Decision-Making in Clinical Practice: Impacts on Prescription Quality - Hossain, Md Shakhawat (Université d'Ottawa | University of Ottawa, 2020)
Ethical decision making in clinical practice is essential to ensure the best health care of the patient. However, sometimes physicians do not make an ethical decision in clinical practice. In some countries the physicians prescribe substandard or unnecessary medicine and recommend an unnecessary pathology examination, hospital or intensive care unit admission, being influenced by receiving gifts from pharmaceutical companies that lead to deteriorating prescription quality, increasing treatment costs, and the patient’s suffering. A physician's prescription contains advice for pathology tests and interventions that need to be followed for the patient’s recovery. As a result, the health care products’ marketing and sales are different than those of the other commodities. Usually, production companies target end-users for marketing and selling purposes, but physicians are the targets in the case of health-related products. In this case, end-users, especially patients, buy products based on physicians’ prescriptions. Therefore, pharmaceutical companies, pathology laboratories, private hospitals, clinics, nursing homes, and research institutes mostly depend on physicians to sell their products to consumers. There is a symbiotic between doctors and pharmaceutical companies. Without pharmaceutical products, doctors cannot help the patient, but on the other hand, the producers of the products also depend on doctors’ prescriptions in earning revenue (Joel 31). Joel defines the relationship between doctors and pharmaceutical companies as a symbiotic relationship. This symbiotic relationship, some view as an unpleasant, illegal type of relationship, they may be failing to see both the necessity and benefits related to it. The companies give gifts like meals, free samples of medications to give out to patients, educational items, or breaks from the office routine. However, each of these gifts impresses the feeling within doctors that they need to reciprocate (Joel 24). As a result, physicians have to make an unethical and unjust decision. The legal and regulatory measures may not always work. In that case, ethical knowledge and practice can act as a self-defending and robust measure. At the time of graduation, the physician takes an oath committing to deliver the best treatment to the patient according to her or his knowledge (Hajar 156). Hippocrates was the first who referred and asserted that the purpose of medicine is to protect the interest of the patient, and it was defined as the code of professional conduct. (Askitopoulou and Vgontzas 1483). For thousands of years, the medical profession had to abide by the Oath of Hippocrates. The oath historically guides the physician’s conduct towards the patient, colleagues, and society. At the beginning of the Hippocratic Oath, a physician declares the following: “I swear by Apollo, the Physician and Aesculapius, and Hygeia and Panacea and all the gods and goddesses, making them my witnesses, that I will fulfill according to my ability and judgment this oath and this covenant” (Hajar 156). The first stanza of the oath reflects the remembrance of the first generation from whom knowledge is gained and commitment to transfer knowledge to the next generation. The second stanza of the oath promises to “apply dietetic measures for the benefit of the sick according to [the doctor’s] ability and judgment” (Hajar 156). Nowadays, many medical schools all over the world use a modern version of the Hippocratic Oath (Hajar 156). The oath of the physician creates a commitment and ethical obligation to the patients that the society commonly believes without any question. The following Table 1 shows the modern version of the Hippocratic Oath.